Phthalate Exposure During the Prenatal and Lactational Period Increases the Susceptibility to Rheumatoid Arthritis in Mice - Elter, Elena; Wagner, Marita; Buchenauer, Lisa; Bauer, Mario; Polte, Tobias (Frontiers in Immunology, 2020)
The prenatal and early postnatal period is highly sensitive to environmental exposures that may interfere with the developmental programming of the immune system leading to an altered disease risk in later life. While the impact of early environmental exposures on the development of e.g. allergic diseases is very well documented, the role of perinatal influences for activation or exacerbation of autoimmune diseases like rheumatoid arthritis (RA) has not yet been clarified. In the present study we investigated the effect of maternal exposure of DBA/1 mice to the plasticizer benzyl butyl phthalate (BBP) on the development of RA in the offspring. Using a mild collagen-induced arthritis (CIA) model, 38% of the offspring from un-exposed dams showed clinical signs of RA. In contrast, the RA prevalence of mice from BBP-exposed dams was increased to 60%. Moreover, the clinical severity of RA was enhanced in the progeny of BBP-exposed dams compared to control animals. Additionally, maternal BBP exposure led to elevated serum IgG1 and IgG2a level in the offspring and increased the IFN-γ and IL-17 release from collagen-re-stimulated spleen cells. Transcriptome analysis of splenoytes isolated from 3-week-old pups before RA-induction revealed considerable changes in gene expression in the offspring from BBP-exposed dams. Among them were regulator of G-protein signaling 1 (rgs1), interleukin-7 receptor (il-7r) and CXC chemokine 4 (cxcr4), all genes that have previously been described as associated with RA pathology. In summary, our results demonstrate that perinatal exposure to BBP increases the susceptibility of the offspring to RA, probably via a phthalate-induced disturbed regulation of RA-relevant genes or signalling pathways.